Low-cost advanced oxidation process catalyst for treating industrial organic wastewater as well as preparation method and application of low-cost advanced oxidation process catalyst

By grinding and ball milling, a iron-manganese bimetallic composite mineral catalyst is prepared and mixed with biochar to form a biochar-supported catalyst, which solves the problems of easy dissolution and poor circulation stability of the existing iron-based catalysts, and achieves an efficient and economical removal of chlorophenol pollutants.

CN119793479AActive Publication Date: 2025-04-11JIANGSU ZHONGKE YUNJING ENVIRONMENTAL TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411894242.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When treating industrial organic wastewater, existing iron-based catalysts have problems such as easy dissolution, poor circulation stability, complex synthesis process and expensive, making it difficult to achieve cost-effective water pollution control.

Method used

By grinding natural iron ore and manganese ore particles and ball milling, a micron-scale iron-manganese bimetallic composite mineral catalyst was prepared and mixed with heterogeneous elements doped biochar to form a biochar supported catalyst for removal of chlorophenol pollutants in advanced oxidation processes.

Benefits of technology

This catalyst has significant cost-effectiveness, stability and reusability. It can efficiently remove chlorophenol pollutants in industrial organic wastewater, with a degradation rate of more than 90%, and is suitable for the treatment of a variety of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793479A_ABST
    Figure CN119793479A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost advanced oxidation process catalyst for treating industrial organic wastewater as well as a preparation method and application thereof, and belongs to the field of preparation of environmental remediation materials and water pollution control. The preparation method of the catalyst is based on biochar and natural iron and manganese minerals, and comprises the following steps: firstly, crushing and sieving natural magnetite and pyrolusite, fully mixing according to a certain proportion, carrying out ball milling treatment, and obtaining miscellaneous element doped biochar by utilizing a pyrolysis method; and fully mixing the mixed element doped biochar and the iron manganese mineral composite catalyst, and then carrying out ball milling treatment under the protection of an inert atmosphere, so as to obtain the composite catalyst. The heteroelement-doped biochar contained in the catalyst promotes aggregation and electron transfer of pollutants, iron and manganese double metal elements can serve as active sites, the activation efficiency is remarkably improved through the synergistic effect of the iron and manganese double metal elements, and the degradation efficiency of the pollutants is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental restoration material preparation and water pollution control, and specifically relates to an advanced oxidation process catalyst for low-cost treatment of industrial organic wastewater and a preparation method and application thereof. Background Art

[0002] One of the environmental problems worldwide is the serious water pollution caused by various persistent organic pollutants discharged from industrial activities. Chlorophenol is a type of persistent organic pollutant. As an important organic solvent and intermediate, it is widely used in the production of pesticides, dyes, medicines, plastics and other chemicals. It exists in most chemical wastewaters, especially in papermaking and textile industrial wastewater. The chemical structure of chlorophenol contains stable chlorine atoms and aromatic rings, and the p-π coupling between Cl and benzene rings makes it difficult to activate the C-Cl bond in chlorophenol, making it extremely stable and difficult to biodegrade in the environment. It seriously threatens human health and environmental safety and has been listed as a priority pollutant by the US Environmental Protection Agency and European regulators.

[0003] In recent decades, different methods have been developed to remove chlorophenol compounds from the environment, which can be divided into three categories: bioremediation technology, physical remediation technology and chemical remediation technology. At present, bioremediation technology and physical remediation technology still have problems such as incomplete removal and insufficient mineralization, so the removal of highly toxic substances is still one of the challenges of current industrial wastewater treatment. Iron-based catalyst catalytic oxidation persulfate advanced oxidation technology has the advantages of strong anti-interference ability and fast reaction rate and has attracted widespread attention. However, the synthesis of various high-performance iron-based catalysts has proved to be complicated and expensive, making them economically impractical. And after a large number of literature surveys, it was found that various synthetic iron-based catalysts have problems such as easy dissolution, poor cyclic stability, and strict pH restrictions. Therefore, it is crucial to study iron-based catalysts that are cost-effective, have a wide range of applications, are easy to recycle and are green and environmentally friendly.

[0004] Many natural iron-containing ores have been used as cheap and easily available iron-based catalysts for persulfate activation, avoiding complex preparation processes and controlling solid waste, and providing a feasible method for the degradation of chlorophenols. Fe3O4, Fe2O3, FeO(OH), FeS2, and FeCO3 in natural iron-containing minerals are the main active components, which can effectively activate persulfate to produce strong oxidative free radicals to promote the degradation of pollutants. In the persulfate activation process, the Fe(II) structure in natural iron-containing minerals plays an important role. Compared with homogeneous Fe 2+ The activation process is different, and the activation of persulfate by Fe(II) mainly occurs on the solid surface, avoiding excessive contact and rapid consumption of Fe(II). However, the Fe(II) content in natural iron-containing minerals is low and the catalytic performance is weak. Summary of the invention

[0005] The purpose of the present invention is to provide a low-cost advanced oxidation process catalyst for treating industrial organic wastewater and a preparation method thereof, so as to overcome the problems of easy dissolution, poor cyclic stability, complex synthesis process and high price of current iron-based catalysts.

[0006] To achieve the above object, the present invention provides the following technical solutions: A low-cost advanced oxidation process catalyst for treating industrial organic wastewater is prepared by a method comprising the following steps: (1) Grinding natural iron ore and natural manganese ore particles respectively and then performing preliminary screening through a 20-mesh sieve; (2) adding the sieved iron ore particles and manganese ore particles obtained in step (1) into a ball mill for ball milling under inert gas protection to obtain ball-milled iron ore powder and manganese ore powder; (3) mixing the iron ore powder and manganese ore powder obtained in step (2) after ball milling in a certain proportion, adding the mixture into a ball mill and performing ball milling again to obtain a micron-sized iron-manganese bimetallic composite mineral catalyst; (4) Fully soaking the biomass in a solution containing a heteroelement reagent, drying the soaked biomass, placing it in a tubular furnace, and pyrolyzing it at a certain temperature for a certain period of time under an inert gas atmosphere to obtain heteroelement-doped biochar; (5) The micron-sized iron-manganese bimetallic composite mineral catalyst obtained in step (3) is mixed with the heteroelement-doped biochar obtained in step (4) and ball-milled under an inert gas to obtain the heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst.

[0007] In step (1) of the above method, the natural iron ore may be specifically magnetite (the active ingredient is Fe3O4, and it also contains impurity elements such as vanadium (V), chromium (Cr), manganese (Mn), magnesium (Mg), zinc (Zn), aluminum (Al), etc., and the magnetic iron content reaches 25.29%), hematite, siderite, ilmenite, pyrite, limonite and iron spinel; the manganese ore may be specifically pyrolusite (the active ingredient is MnO2, and it also contains impurities such as Fe2O3, MgO, Al2O3, CaO, SiO2, etc., and the manganese content reaches 21.63%), psilomelane, manganese ore, brown manganese ore, hausmannite, rhodochrosite and manganese spinel; The grinding bodies used in the ball milling treatment in steps (2) and (3) are zirconium oxide balls, and the weight ratio of the zirconium oxide balls to the mineral is 30-60:1, specifically 45:1; Preferably, in steps (2) and (3), the inert gas used in the ball milling treatment is N2 or Ar, the purging time is 15-45 min, specifically 30 min, the ball milling speed is 200-600 rpm, specifically 400 rpm, and the ball milling time is 8-16 h, specifically 12 h.

[0008] Preferably, the particle size of the iron ore powder and the manganese ore powder after ball milling in step (2) is in the range of 0-8 μm, and the endpoint 0 is not desirable.

[0009] Preferably, the mixing ratio (mass ratio) of the iron ore powder and the manganese ore powder in step (3) is 3:1-1:3, specifically 3:1, 2:1, 1:1, 1:2 and 1:3.

[0010] Preferably, the particle size of the micron-sized iron-manganese bimetallic composite mineral catalyst in step (3) is in the range of 0 to 3.5 μm, and the endpoint 0 is not desirable.

[0011] In step (4), the heteroelement may be at least one of nitrogen, phosphorus and sulfur; the solution containing the heteroelement reagent may be a solution of at least one compound selected from urea, phosphoric acid, phytic acid and thiourea, or a composite solution of multiple compounds; The biomass may be at least one of waste wood, straw, rice husk and coconut husk; Preferably, the heteroelement reagent is urea, and the biomass is straw; The mass ratio of urea to straw is 3:1-1:3, specifically 3:1, 2:1, 1:1, 1:2 and 1:3, more specifically 1:2; The soaking time may be 8-16 hours, specifically 12 hours; The drying time is 12-14 hours, specifically 12 hours; The inert gas used in the tubular furnace calcination process is N2, the calcination time is 2-6 hours, specifically 4 hours, and the temperature is 600-1200°C, specifically 600°C.

[0012] Preferably, in step (5), the mass ratio of the biochar doped with heteroelements to the micron-sized iron-manganese bimetallic composite mineral catalyst may be 3:1-1:3, specifically 3:1, 2:1, 1:1, 1:2 or 1:3.

[0013] The grinding body used in the ball mill is a zirconia ball, and the weight ratio of the zirconia ball to the mixture is 30-60:1, specifically 45:1; The inert gas used in the ball milling treatment is N2 or Ar, specifically N2, the purge time is 15-45 min, specifically 30 min, the ball milling speed is 200-600 rpm, specifically 400 rpm, and the ball milling time is 8-16 h, specifically 12 h.

[0014] The heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst prepared by the above method also falls within the protection scope of the present invention.

[0015] The application of the above-mentioned heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst in the advanced oxidation treatment of industrial organic wastewater also falls within the protection scope of the present invention.

[0016] In the application, the hetero-element-doped biochar loaded with a micron-sized iron-manganese bimetallic composite mineral catalyst is used to activate persulfate to degrade chlorophenol organic pollutants in industrial organic wastewater; In the application, the persulfate may be peroxymonosulfate (ammonium persulfate, potassium persulfate and sodium persulfate) and peroxydisulfate (ammonium persulfate, potassium persulfate and sodium persulfate); The chlorophenol organic pollutants include 2,4-dichlorophenol, 2,4,6-trichlorophenol and pentachlorophenol; The dosage of the heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst is 0.5-3 g / L, the persulfate concentration is 3-15 mM, and the initial concentration of chlorophenol organic pollutants in chlorophenol organic wastewater is 1-20 mg / L.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes natural minerals and waste biomass that are widely present and easily available in nature as a matrix to prepare low-cost and high-efficiency catalysts, which not only has significant cost-effectiveness, but also plays a role in controlling solid waste and promoting the sustainable utilization of resources, and has certain theoretical and practical significance.

[0018] (2) The natural iron ore used in the present invention can stably accommodate the presence of Fe(II) and Fe(III), and is homogeneous with Fe 2+ The activation process is different. The activation of persulfate by structural Fe(II) mainly occurs on the mineral surface, which avoids excessive contact and rapid consumption of Fe(II) and greatly improves the catalytic efficiency.

[0019] (3) The present invention constructs a micron-sized iron-manganese bimetallic composite mineral catalyst by introducing natural manganese ore. Fe(II), Mn(II) and Mn(III) can all act as electron donors to activate persulfate. The rapid redox cycle between the two can achieve continuous replenishment of catalytic active sites, thereby promoting the activation of persulfate and the degradation of pollutants.

[0020] (4) The present invention introduces heteroelement-doped biochar to construct a highly conductive biochar-loaded iron-manganese bimetallic mineral catalyst, which promotes the adsorption capacity and removal efficiency of the composite material for pollutants, enhances the electron transfer of Fe(II), Mn(II) and Mn(III) to persulfate and the degradation of pollutants.

[0021] (5) The catalyst prepared by the present invention has excellent stability and reusability, overcoming the problems of easy dissolution and poor cyclic stability of traditional iron-based catalysts. After five cycles of use, the degradation rate of pollutants is still over 90%, showing significant catalytic activity. In addition, the catalyst exhibits excellent degradation effects on a variety of organic pollutants, showing its broad application prospects in the field of industrial organic wastewater treatment.

[0022] (6) The present invention adopts ball milling and pyrolysis treatment to prepare the catalyst, which has a simple preparation process, convenient operation and is suitable for large-scale application. The present invention reduces the size of iron ore through ball milling process to enhance the exposure of active ingredients; secondly, the catalytic performance of the catalyst is optimized by introducing natural manganese ore to construct iron-manganese bimetallic composite minerals, giving full play to the synergistic effect of iron-manganese bimetallic; in addition, by pyrolysis of waste biomass to obtain highly conductive biochar, the removal rate of pollutants and the electron transfer rate of the composite material are further promoted, the mineralization capacity of pollutants is improved, and the efficient treatment of industrial organic wastewater can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of nitrogen-doped biochar loaded with micron-sized iron-manganese mineral composite catalyst.

[0024] Figure 2 This is the EDS energy spectrum of nitrogen-doped biochar loaded with micron-sized iron-manganese mineral composite catalyst.

[0025] Figure 3 This is the XRD pattern of nitrogen-doped biochar-supported micron-sized iron-manganese mineral composite catalyst.

[0026] Figure 4 This is the hysteresis loop diagram of nitrogen-doped biochar-loaded micron-sized iron-manganese mineral composite catalyst.

[0027] Figure 5 It is the intermediate ion fragment in the degradation system.

[0028] Figure 6 This is the result of biotoxicity assessment of degradation intermediates to fish.

[0029] Figure 7 This is the result of biotoxicity assessment of the degradation intermediates to Daphnia.

[0030] Figure 8 The results are the biotoxicity assessment results of the degradation intermediates to green algae. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0032] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0033] Example 1 (1) In a N2 atmosphere, natural magnetite particles and natural pyrolusite particles that had been ground through a 20-mesh sieve were added to a zirconia jar for ball milling (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of mineral addition to zirconia ball of 1:45) to obtain micron-sized magnetite powder (0-8 μm, endpoint 0 is undesirable) and manganese ore powder (0-8 μm, endpoint 0 is undesirable). The obtained magnetite powder and pyrolusite powder were fully mixed at a mass ratio of 3:1, added to a zirconia jar for ball milling again for 12 h (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of zirconia ball to mineral of 45:1), and a micron-sized iron-manganese composite mineral catalyst (0-3.5 μm, endpoint 0 is undesirable) with a mass ratio of magnetite to pyrolusite of 3:1 was obtained.

[0034] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0035] Example 2 Compared with Example 1, the difference is that the synthesis ratio is different.

[0036] (1) Under N2 atmosphere, natural magnetite particles and natural pyrolusite particles after passing through a 20-mesh sieve were added to a zirconia jar for ball milling (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of mineral addition to zirconia ball of 1:45) to obtain ball-milled magnetite powder (0-8 μm, endpoint 0 is undesirable) and pyrolusite powder (0-8 μm, endpoint 0 is undesirable). The obtained magnetite powder and pyrolusite powder were fully mixed at a mass ratio of 2:1, added to a zirconia jar for ball milling again for 12 h (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of zirconia ball to mineral of 45:1), and a micron-sized iron-manganese composite mineral catalyst (particle size 0-3.5 μm, endpoint 0 is undesirable) with a mass ratio of magnetite to pyrolusite of 2:1 was obtained.

[0037] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0038] Example 3 Compared with Example 1, the difference is that the synthesis ratio is different.

[0039] (1) Under N2 atmosphere, natural magnetite particles and natural pyrolusite particles after passing through a 20-mesh sieve were added to a zirconia jar for ball milling (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of mineral addition to zirconia ball of 1:45) to obtain ball-milled magnetite powder (0-8 μm, endpoint 0 is undesirable) and pyrolusite powder (0-8 μm, endpoint 0 is undesirable). The obtained magnetite powder and manganese ore powder were fully mixed at a mass ratio of 1:1, added to a zirconia jar for ball milling again for 12 h (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of zirconia ball to mineral of 45:1), and a micron-sized iron-manganese composite mineral catalyst (particle size 0-3.5 μm, endpoint 0 is undesirable) with a mass ratio of magnetite to pyrolusite of 1:1 was obtained.

[0040] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0041] Example 4 Compared with Example 1, the difference is that the synthesis ratio is different.

[0042] (1) Under N2 atmosphere, natural magnetite particles and natural pyrolusite particles after passing through a 20-mesh sieve were added to a zirconia jar for ball milling (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mineral 1:45) to obtain ball-milled magnetite powder (0-8 μm, endpoint 0 is not desirable) and pyrolusite powder (0-8 μm, endpoint 0 is not desirable). The obtained magnetite powder and manganese ore powder were fully mixed in a mass ratio of 1:2, added to a zirconia jar and ball milled again for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of mineral addition to zirconia ball 45:1), and a micron-sized iron-manganese composite mineral catalyst (particle size 0-3.5 μm, endpoint 0 is not desirable) with a mass ratio of magnetite:pyrolusite of 1:2 was obtained.

[0043] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0044] Example 5 Compared with Example 1, the difference is that the synthesis ratio is different.

[0045] (1) Under N2 atmosphere, natural magnetite particles and natural pyrolusite particles after passing through a 20-mesh sieve were added to a zirconia jar for ball milling (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of mineral addition to zirconia ball of 1:45) to obtain ball-milled magnetite powder (0-8 μm, endpoint 0 is undesirable) and pyrolusite powder (0-8 μm, endpoint 0 is undesirable). The obtained magnetite powder and manganese ore powder were fully mixed at a mass ratio of 1:3, added to a zirconia jar for ball milling again for 12 h (ball milling speed of 400 rpm, ball milling time of 12 h, weight ratio of zirconia ball to mineral of 45:1), and a micron-sized iron-manganese composite mineral catalyst (particle size 0-3.5 μm, endpoint 0 is undesirable) with a mass ratio of magnetite to pyrolusite of 1:3 was obtained.

[0046] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0047] The degradation rates and reaction rate constants of Examples 1-5 are shown in Table 1 below: Table 1

[0048] As shown in Table 1, the ratio of magnetite to pyrolusite has a significant effect on the catalytic performance of the obtained catalyst, among which the catalyst obtained by ball milling magnetite and pyrolusite in a mass ratio of 1:1 has the best catalytic activity.

[0049] Example 6 Compared with Example 3, the difference lies in that the synthetic components are different.

[0050] (1) Weigh 5 g of urea and dissolve it in deionized water. Then immerse 10 g of corn straw powder in it for 12 h and then put it in an oven to dry for 12 h. After drying, put it in a tubular furnace and calcine it in a N2 atmosphere for 4 h at a temperature of 600 °C to obtain nitrogen-doped biochar.

[0051] (2) Under N2 atmosphere, nitrogen-doped biochar and the optimal proportion of iron-manganese composite mineral catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added to a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain nitrogen-doped biochar loaded with micron-sized iron-manganese composite mineral catalyst in a mass ratio of 3:1:1 of nitrogen-doped biochar: magnetite: pyrolusite.

[0052] The prepared nitrogen-doped biochar-supported micron-sized iron-manganese composite mineral catalyst was subjected to a series of characterizations to evaluate the catalytic performance of the catalyst. The SEM characterization results are shown in Figure 1 As shown, the EDS spectrum analysis results are as follows Figure 2 The XRD characterization results are shown in Figure 3 The hysteresis loop characterization results are shown in Figure 4 shown.

[0053] (3) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0054] Example 7 Compared with Example 6, the difference is that the synthesis ratio is different.

[0055] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 2:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst in a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 2:1:1.

[0056] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0057] Example 8 Compared with Example 6, the difference is that the synthesis ratio is different.

[0058] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 1:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst in a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 1:1:1.

[0059] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0060] Example 9 Compared with Example 6, the difference is that the synthesis ratio is different.

[0061] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese composite mineral catalyst prepared in Example 3 were fully mixed in a mass ratio of 1:2 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar loaded with micron-sized iron-manganese composite mineral catalyst in a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 1:2:2.

[0062] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0063] Example 10 Compared with Example 6, the difference is that the synthesis ratio is different.

[0064] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese composite mineral catalyst prepared in Example 3 were fully mixed in a mass ratio of 1:3 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar loaded with micron-sized iron-manganese composite mineral catalyst in a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 1:3:3.

[0065] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0066] Comparative Example 1 Compared with Examples 6-10, the difference is that the synthetic components of biochar are different.

[0067] (1) Weigh 10 g of corn straw powder and place it in a tubular furnace for calcination at 600 °C in a N2 atmosphere for 4 h to obtain biochar without doping with impurities.

[0068] (2) The biochar prepared above and the optimal ratio of iron-manganese composite mineral catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a biochar-loaded micron-sized iron-manganese composite mineral catalyst with a mass ratio of biochar: magnetite: pyrolusite of 3:1:1.

[0069] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C.

[0070] The removal rates and reaction rate constants of Examples 6-10 and Comparative Example 1 are shown in Table 2 below: Table 2

[0071] As can be seen from Table 2, adding biochar as a carrier has a significant effect on the catalytic performance of the obtained catalyst, and the catalyst prepared with nitrogen-doped biochar as a carrier has higher catalytic activity. Among them, the catalyst prepared by ball milling with a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 3:1:1 has the highest catalytic activity.

[0072] Embodiment 11 Compared with Example 10, the difference is that different pollutants are used to test the practical applicability of the catalyst.

[0073] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst with a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 3:1:1.

[0074] (2) Chloramphenicol, triclosan and bisphenol A were selected as representative organic substances for catalytic degradation performance tests to evaluate the catalyst's ability to remove different pollutants. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed into 100 mL of chloramphenicol, triclosan and bisphenol A aqueous solutions (10 mg / L) respectively. Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentrations of chloramphenicol, triclosan and bisphenol A in the solution at different times were determined using a high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C. The degradation results are shown in Table 3: Table 3

[0075] Example 12 Compared with Example 10, the difference is that the recyclability of the catalyst is tested by a cycle test.

[0076] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst with a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 3:1:1.

[0077] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The concentration of 2,4,6-trichlorophenol in the solution at different times was determined by high performance liquid chromatography (HPLC). The chromatographic column was a C18 column with a specification of 4.6×250 mm, 5 μm, and the column temperature was maintained at 30°C. After each round of catalytic experiments, the catalyst was recollected by magnetic separation. The collected catalyst was washed with deionized water and ethanol three times to remove surface impurities and dried in a freeze dryer for 12 h. The cycle test was carried out and repeated 5 times to evaluate the stability of the catalyst in activating persulfate to degrade 2,4,6-trichlorophenol. The degradation results are shown in Table 4: Table 4

[0078] Example 13 Compared with Example 10, the difference is that the TOC removal rate in the catalytic reaction system was tested to evaluate the mineralization ability of the nitrogen-doped biochar-loaded iron-manganese mineral composite catalyst-activated persulfate system for 2,4,6-trichlorophenol.

[0079] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst with a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 3:1:1.

[0080] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 20 min, 40 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 15 mL of the supernatant was collected and filtered with a 0.22 μm PTFE membrane. The filtered sample was placed in a centrifuge tube containing 50 μL of methanol for timely quenching, and the TOC content in the system was measured using a total organic carbon analyzer (Sievers M9). The mineralization results are shown in Table 5.

[0081] Table 5

[0082] Embodiment 14 Compared with Example 10, the difference is that the intermediates produced by 2,4,6-trichlorophenol during the catalytic reaction were identified and characterized, and the toxicity of the intermediates was analyzed to evaluate the safety of nitrogen-doped biochar-loaded iron-manganese mineral composite catalyst for repairing organic polluted wastewater.

[0083] (1) Under N2 atmosphere, the nitrogen-doped biochar prepared in Example 6 and the optimal ratio of iron-manganese mineral composite catalyst prepared in Example 3 were fully mixed in a mass ratio of 3:1 and added into a zirconia tank for ball milling for 12 h (ball milling speed 400 rpm, ball milling time 12 h, weight ratio of zirconia ball to mixture 45:1) to obtain a nitrogen-doped biochar-loaded micron-sized iron-manganese composite mineral catalyst with a mass ratio of nitrogen-doped biochar: magnetite: pyrolusite of 3:1:1.

[0084] (2) 2,4,6-Trichlorophenol was selected as the characteristic pollutant for catalytic degradation performance test. The degradation experiment was carried out in a 150 mL brown serum vial, and the bottle mouth was sealed with a butyl rubber stopper. The specific steps are as follows: First, 0.25 g of catalyst (2.5 g / L, vacuum sealed) was weighed and dispersed in 100 mL of 2,4,6-trichlorophenol aqueous solution (10 mg / L). Subsequently, 0.27 g of ammonium persulfate (12 mM) was added to start the reaction and the serum bottle was sealed. The above serum bottle was placed in a constant temperature shaking box at 25°C and the experiment was carried out at a speed of 180 r / min. Samples were taken from the reaction mixture at specific times (0 min, 20 min, 40 min, 60 min), and the catalyst material was separated by magnetic separation technology. Subsequently, 1.2 mL of the supernatant was collected and filtered through a 0.22 μm PTFE membrane. The filtered sample was placed in a liquid chromatography injection bottle containing 50 μL of methanol and quenched in time. The degradation intermediates in the solution at different times were identified by liquid chromatography tandem mass spectrometry (LC-MS, Xevo G2 Qtof). The analysis was performed by negative ion mass spectrometry scanning in the range of 50 ~ 500 m / z. The detection conditions were as follows: Kinetex C18 column (2.6 μm, 100×2.1 mm, USA); the mobile phase was acetonitrile (0.1% formic acid, phase A) and water (0.1% formic acid, phase B), the flow rate was 0.3 mL / min; the injection volume was 2 μL; the gradient elution program (min, B%) was (0, 95), (1, 95), (6, 50), (10, 20), (13, 10), (15, 90) and (20, 95). Subsequently, the biological toxicity of 2,4,6-trichlorophenol and its intermediates was evaluated using ECOSAR software. Figure 5 As shown in Figure 1, a total of 16 ion fragments and intermediates were detected in the system. Figure 6 , Figure 7 , Figure 8 It can be seen that all intermediates are effectively cleaved in the subsequent continuous degradation to form low molecular weight products, which significantly reduces their biological toxicity and eventually reaches a harmless level.

[0085] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A low-cost advanced oxidation process catalyst for treating industrial organic wastewater, prepared by a method comprising the following steps: (1) Grinding natural iron ore and natural manganese ore particles respectively and then performing preliminary screening through a 20-mesh sieve; (2) adding the sieved iron ore particles and manganese ore particles obtained in step (1) into a ball mill for ball milling under inert gas protection to obtain ball-milled iron ore powder and manganese ore powder; (3) mixing the iron ore powder and manganese ore powder obtained in step (2) after ball milling in a certain proportion, adding the mixture into a ball mill and performing ball milling again to obtain a micron-sized iron-manganese bimetallic composite mineral catalyst; (4) Fully soaking the biomass in a solution containing a heteroelement reagent, drying the soaked biomass, placing it in a tubular furnace, and pyrolyzing it at a certain temperature for a certain period of time under an inert gas atmosphere to obtain heteroelement-doped biochar; (5) The micron-sized iron-manganese bimetallic composite mineral catalyst obtained in step (3) is mixed with the heteroelement-doped biochar obtained in step (4) and ball-milled under an inert gas to obtain the heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst.

2. The catalyst according to claim 1, characterized in that In step (1), the natural iron ore is at least one of magnetite, hematite, siderite, ilmenite, pyrite, limonite and iron spinel; the manganese ore is at least one of pyrolusite, psilomelane, manganese ore, limonite, hausmannite, rhodochrosite and manganese spinel; The grinding bodies used in the ball milling treatment in steps (2) and (3) are zirconium oxide balls, and the weight ratio of the zirconium oxide balls to the added mineral is 30-60:1; The ball milling speed is 200-600rpm, and the ball milling time is 8-16h.

3. The catalyst according to claim 1, characterized in that The particle size of the iron ore powder and the manganese ore powder after ball milling in step (2) is in the range of 0 to 8 μm, and the endpoint 0 is not desirable; In step (3), the mixing mass ratio of the iron ore powder to the manganese ore powder is 3:1-1:

3.

4. The catalyst according to claim 3, characterized in that In step (3), the mixing mass ratio of the iron ore powder to the manganese ore powder is 1:

1.

5. The catalyst according to claim 3, characterized in that The particle size of the micron-sized iron-manganese bimetallic composite mineral catalyst in step (3) is in the range of 0 to 3.5 μm, and the endpoint 0 is not desirable.

6. The catalyst according to claim 1, characterized in that The heteroelement is at least one of nitrogen, phosphorus and sulfur; the solution containing the heteroelement reagent is a solution of at least one compound selected from urea, phosphoric acid, phytic acid and thiourea or a composite solution of multiple compounds; The biomass is at least one of waste wood, straw, rice husk and coconut husk.

7. The catalyst according to claim 6, characterized in that The heteroelement reagent is urea, and the biomass is straw; The mass ratio of urea to straw is 3:1-1:3; The soaking time is 8-16h; Drying time is 12-14h; The inert gas used in the tubular furnace calcination process is N2, the calcination time is 2-6h, and the temperature is 600-1200℃.

8. The catalyst according to claim 1, characterized in that In step (5), the mass ratio of the biochar doped with heteroelement to the micron-sized iron-manganese bimetallic composite mineral catalyst is 3:1-1:

3.

9. Use of the catalyst according to any one of claims 1 to 8 in advanced oxidation treatment of industrial organic wastewater.

10. The use according to claim 9, characterized in that: In the application, the hetero-element-doped biochar loaded with a micron-sized iron-manganese bimetallic composite mineral catalyst is used to activate persulfate to degrade chlorophenol organic pollutants in industrial organic wastewater; In the application, the persulfate is peroxymonosulfate and peroxydisulfate; The chlorophenol organic pollutants include 2,4-dichlorophenol, 2,4,6-trichlorophenol and pentachlorophenol; The dosage of the heteroelement-doped biochar-loaded micron-sized iron-manganese bimetallic composite mineral catalyst is 0.5-3 g / L, the persulfate concentration is 3-15 mM, and the initial concentration of chlorophenol organic pollutants in chlorophenol organic wastewater is 1-20 mg / L.

Citation Information

Patent Citations

  • Charcoal supported ferro-manganese dual-metal oxide optical Fenton composite material and preparation method thereof

    CN109364940A

  • Ferro-manganese double metal oxide modified bio-carbon photo-Fenton composite material and preparation method thereof

    CN109675581A

  • Novel catalytic adsorption material prepared on basis of natural minerals and biomass

    CN111921536A

  • Method for treating arsenic-containing waste acid by cooperation of hematite and manganese sand

    CN112028331A

  • Remediation agent and remediation method for organic contaminated soil

    CN112756392A

Cited By

  • Simple preparation method and application of tailing-based composite catalyst

    CN122209423A